2021
DOI: 10.3390/resources10120118
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of Lignocellulosic Biomass with 1-Ethyl-3-methylimidazolium Acetate for Its Eventual Valorization by Anaerobic Digestion

Abstract: This study assessed the breakdown of lignocellulosic biomass (LB) with the ionic liquid (IL) 1-ethyl-3-methylimidazolium acetate ([Emim][Ac]) as a pretreatment to increase the methane yield. The pretreatment was conducted for wheat straw (WS), barley straw (BS), and grape stem (GS) at 120 °C for 120 min, using several LB to [Emim][Ac] ratios (1:1, 1:3, and 1:5 w/w). Pretreatment significantly disrupted the lignocellulose matrix of each biomass into soluble sugars. GS showed the highest sugar yield, which was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
2
2
0
Order By: Relevance
“…The decomposition rates were very low and became negligible after this stage. Similar results were found by the authors (Marin-Batista et al 2021;Siddiqi et al 2022). The TGA curves indicated that there was less degradation residue (char) from the pretreated straw than from the untreated straw.…”
Section: Thermal Analysessupporting
confidence: 88%
See 1 more Smart Citation
“…The decomposition rates were very low and became negligible after this stage. Similar results were found by the authors (Marin-Batista et al 2021;Siddiqi et al 2022). The TGA curves indicated that there was less degradation residue (char) from the pretreated straw than from the untreated straw.…”
Section: Thermal Analysessupporting
confidence: 88%
“…The maximum peaks in the DTG profiles for the different samples occurred in this stage and were detected in the temperature range 300 to 320 °C due to exothermic reactions of the cellulose. Moreover, the peaks for the pretreated samples were greater than those for the untreated samples, which was explained by the increased cellulose proportion after pretreatment, similar to the findings of Marin-Batista et al (2021).…”
Section: Thermal Analysessupporting
confidence: 78%
“…[Cl]), were studied [37][38][39][40]. To reflect the environment of the enzymatic hydrolysis of biomass pretreated with ILs, we have added 10% v/v of ILs to the reaction mixture.…”
Section: Ils Previously Used In Many Investigations Into Biomass Trea...mentioning
confidence: 99%
“…Since a much higher glucose yield was obtained in the presence of 24 mg (19 U) of cellulase from A. niger, we decided to use the amounts of all biocatalysts that correspond to the same activity (19 U) for further studies. ), were studied [37][38][39][40]. To reflect the environment of the enzymatic hydrolysis of biomass pretreated with ILs, we have added 10% v/v of ILs to the reaction mixture.…”
Section: Ils Previously Used In Many Investigations Into Biomass Trea...mentioning
confidence: 99%